Managing Bobwhites in the Cutover Pinelands of South Florida - William H. Moore (National Quail Symposium Proceedings, 2017)
Because the principles governing production of quail are similar throughout its range, only problems and techniques unique to the flat-woods of southwest Florida are discussed. A description of these pine-lands includes geology and soils, climate and key plant communities. The Florida bobwhite and its foods and other needs are discussed briefly. A major portion of the text is concerned with the effects of primary land uses on quail habitat, and management modifications to improve quail production.